2002
DOI: 10.1177/0018726702553002
|View full text |Cite
|
Sign up to set email alerts
|

Letters of Recommendation: An Evolutionary Psychological Perspective

Abstract: This article develops a theoretical framework for understanding the appeal and tone of letters of recommendation using an evolutionary psychological perspective. Several hypotheses derived from this framework are developed and tested. The authors’ theoretical argument makes two major points. First, over the course of human evolution, people developed a preference for narrative information about people, and the format of letters of recommendation is compatible with that preference. Second, because recommenders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Therefore, many of the practices that exist in modern organizations, particularly those that persist despite organizational researchers' insistence that they are problematic, are likely to be understood with more research on how evolved mechanisms guide behavior towards activities that people find inherently rewarding (Colarelli, 2003). The widespread use of the employment interview, for example, may be due to our evolved preference for acquiring information about other people through FtF interaction (Colarelli, 2003;Colarelli, Hechanova-Alampay, & Canali, 2002). The difficulty that women have in integrating themselves into male coalitions is probably another example of evolved mechanisms influencing organizational practices.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many of the practices that exist in modern organizations, particularly those that persist despite organizational researchers' insistence that they are problematic, are likely to be understood with more research on how evolved mechanisms guide behavior towards activities that people find inherently rewarding (Colarelli, 2003). The widespread use of the employment interview, for example, may be due to our evolved preference for acquiring information about other people through FtF interaction (Colarelli, 2003;Colarelli, Hechanova-Alampay, & Canali, 2002). The difficulty that women have in integrating themselves into male coalitions is probably another example of evolved mechanisms influencing organizational practices.…”
Section: Discussionmentioning
confidence: 99%
“…Although LORs have not generated voluminous research (roughly 130 psycINFO hits over 82 years), many aspects of LORs have been explored. Past research has studied factors biasing letters (e.g., Colarelli, Hechanova-Alampay, & Canali, 2002), letter inflation (e.g., Miller & Van Rybroek, 1988), writer characteristics (e.g., Judge & Higgins, 1998), and legal issues surrounding LOR usage (e.g., Range, Menyhert, Walsh, Hardin, Ellis, & Craddick, 1991). Several researchers have recently articulated specific areas of concern regarding LORs (see Aamodt, 2005), and we believe that these areas also represent the theoretical domain of LOR research well.…”
Section: Introductionmentioning
confidence: 86%
“…The form points to different types of knowledge. Studies have shown that, for example, knowledge describing individual events may be preferred over statistical knowledge describing how such events in general occur (Colarelli et al, 2002). The essence of the information may sometimes deviate from the essence of the phenomenon that the information is supposed to describe in the opinion of the information user (e.g., complex matters are presented in a simple fashion).…”
Section: Challenges Of Performance Information Usementioning
confidence: 99%